Die hard collection : 5 movies [videorecording (DVD)] - Stuart, Jeb; De Souza, Steve; Willis, Bruce, 1955-; Rickman, Alan; Godunov, Alexander, 1949-1995; Bedelia, Bonnie, 1946-; Veljohnson, Reginald, 1952-; Richardson, Doug, 1959-; Atherton, William; Sadler, William, 1950-; Amos, John, 1939-; Nero, Franco; et al. (Twentieth Century Fox Home Entertainment, 2016)
Die hard (1988): NYPD police officer John McClane tries to save his wife and several others taken hostage by terrorists during a Christmas party at the Nakatomi Plaza in Los Angeles.